Attitudes of University Students Regarding Potential Conflicts in Socially Responsible Companies. (May 2016) - Barrena-Martinez, Jesus; Lopez-Fernandez, Macarena; Marquez-Moreno, Cristina; Romero-Fernandez, Pedro Miguel
Corporate social responsibility (CSR) is increasingly viewed as a strategic management tool for companies to draw in candidates. In this arena, international responsible rankings such as 'The Great Place to Work', 'Family Responsible Employer Index (FREE)' or 'The Best Companies for Working Mothers' put emphasis on the value of responsible behaviours, not only for surviving in the market, but also to 'win the war for talent'. Using a sample of Spanish University students, this research aims to analyse the process of selecting responsible organizations to work and whether there is a possible future conflict of interest by students between their own and organizational values. Surprisingly, the university students assessed two opposing situations with the highest values: of looking to change employer and of letting time pass in order to ignore the conflict. The implications of the students' assessments and the related factors which affect their decision-making criteria are explored in this article.